Implementation of Good Corporate Governance in Improving Public Services at Blambangan Banyuwangi Hospital - Budi Prambodo; Ika Devy Pramudiana; Amirul Mustofa; Widyawati Widyawati; Damajanti Sri Lestari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to describe and analyze: The Implementation of Good Corporate Governance in Improving Public Services at Blambangan Banyuwangi Hospital. The type of research used is qualitative research. The data analysis technique in the study uses techniques developed by McNabb (2002), namely Grouping the data according to key constructs, Identifying bases for interpretation, Developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that in principle, the implementation of Good Corporate Governance (GCG) at Blambangan Banyuwangi Hospital has gone well, but there are still things that need to be improved. In the principle of accountability, Blambangan Banyuwangi Hospital has implemented it well. This is shown by the organizational structure and clear duties and responsibilities by providing a job description. The hospital conducts performance evaluations on employees. The reward and punishment system has been implemented in the company well. On the principle of accountability, Blambangan Banyuwangi Hospital is well responsible because nurses and employees carry out their duties based on the law. The hospital delivers LAKIP every year. In the principle of responsibility, Blambangan Banyuwangi Hospital has accounted for all related resources within the scope of the hospital to comply with the policies and regulations that apply in the hospital. In the provision of services in hospitals, there are duties and functions of each of the related elements in the hospital. On the principle of independence, Blambangan Banyuwangi Hospital has managed services professionally by not including the involvement of the owner's family to make a decision. On the principle of fairness, Blambangan Banyuwangi Hospital has provided an opportunity for all stakeholders to give their suggestions and opinions to advance the hospital. In the principle of service transparency at Blambangan Banyuwangi Hospital, the availability of service information is substantially adequate and the media for its presentation, the certainty of service time, the cost of e-services that are not transparent and the available service complaint mechanism. Then connected to the website of the hospital, the entity already has a website which contains information about the facilities provided by the hospital and information about the doctors who serve, etc.